Comprehensive space management and treatment of a patient with an early traumatic missing maxillary central incisor: a case report - Liren Chen; Zhiqiang Ouyang; Fen Yao (BMC Oral Health)
Abstract Background For patients missing the maxillary central incisor in childhood, resorption of the alveolar bone in the area of the missing teeth over time can increase the difficulty of performing later prosthodontic treatments. Early loss of permanent teeth is also one of the main causes of malocclusion. Early and effective space management will have a positive effect on the child’s psychological and facial development. Moving the adjacent teeth to the central incisors may help to maintain the alveolar bone in the space of missing teeth, thereby preventing the development or complication of malocclusion. In the present report, we describe a case in which orthodontic treatment was performed for space management due to early missing teeth, leading to successful profile restoration of the missing teeth when she reached adulthood. Case presentation The patient was an 11-year-old girl who underwent replacement dentition due to the loss of her maxillary right central incisor arising from trauma. Her maxillary right lateral incisor was moved to the position of the maxillary right central incisor, necessitating a secondary orthodontic treatment by clear aligner in the permanent dentition. In adulthood, the lateral incisor was reshaped into a central incisor to match the shape of the contralateral central incisor. Early orthodontic treatment took 15 months and the secondary orthodontic treatment took 30 months. The results of one-year follow-up observation confirmed good periodontal condition and occlusion of the anterior teeth. Conclusions This case illustrates the need for early and effective space management through sequential orthodontic treatment and combined prosthodontic treatment to ensure favorable outcomes for patients with missing maxillary central incisors during the mixed dentition period.